ASSESSING THE EFFECT OF DIVIDEND POLICY ON CORPORATE VALUE IN THE ASEAN FINANCIAL SECTOR - Behzodjon Hazratov; Nono Supriatna; Ikin Solikin (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study examines the effect of dividend policy operationalized through the dividend payout ratio (DPR), dividend per share (DPS), and dividend yield (DY) on corporate value among banks operating in Indonesia, Malaysia, and Singapore over the period 2020 to 2024. Using a quantitative approach based on secondary financial data from 370 firm-year observations, simple linear regression analysis was employed. The empirical results indicate that dividend policy, as measured by a composite index, does not exert a statistically significant effect on corporate value (F = 0.244; Sig. = 0.621; R² = 0.001). These findings suggest that corporate value in ASEAN banking institutions is determined by a broader set of factors beyond dividend distribution alone, including regulatory capital constraints, profitability, and macroeconomic conditions. The results are theoretically consistent with the Dividend Irrelevance Theory proposed by Modigliani and Miller (1961) and are corroborated by the stringent capital adequacy frameworks mandated by Basel III. This study contributes to the growing body of comparative financial research on ASEAN banking markets and recommends that future research incorporate additional firm-level and institutional determinants to achieve a more comprehensive model of dividend behavior in regulated financial sectors.